Imaging the Thickness of Passivation Layers for Crystalline Silicon with Micron‐Scale Spatial Resolution Using Spectral Photoluminescence. Issue 11 (30th October 2017) - Nguyen, Hieu T.; Johnston, Steve; Basnet, Rabin; Guthrey, Harvey; Dippo, Pat; Zhang, Hanyu; Al‐Jassim, Mowafak M.; Macdonald, Daniel
Abstract : Thin films deposited on crystalline silicon surfaces are critical components of many silicon‐based devices, including high‐efficiency photovoltaic cells. Knowledge of their optical and electronic properties is important in designing and fabricating efficient solar cells, especially as the device complexity increases and includes micron‐scale features. Here, a camera‐based photoluminescence (PL) technique is developed to image the thickness of specific passivating films on silicon wafers. The technique is entirely contactless and nondestructive, requires minimal sample preparation, and provides a large dynamic range in terms of field of view, with micron‐scale spatial resolution possible. It retains the advantages of PL imaging, a mainstream technique for photovoltaic material and device characterization, and it has some extra capabilities similar to those of ellipsometry. This newly developed technique is demonstrated on hydrogenated amorphous silicon and silicon nitride films, two important passivation technologies for high‐efficiency silicon solar cells. Abstract : Here, a camera‐based photoluminescence technique to image the thickness of specific passivating films on silicon wafers is developed, utilizing the distinct luminescence peaks of these films. The technique is entirely contactless and nondestructive, requires minimal sample preparation, and provides a large dynamic range in terms of field of view, with micron‐scale spatial resolution possible.